Political Connections and Cost of Debt Financing: Empirical Evidence from China - Harjan, Sinan Abdullah; Teng, Min; Shah, Sayyed Sadaqat Hussain; Mohammed, Jamal Hadash (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to investigate whether politically connected firms play a significant role in cost of debt financing. To emphasize this evidence, we empirically analyzed the panel data of the period 2011-2013. We found that politically connected firms have a negative and significant impact on the cost of debt financing compared to Non- politically connected firms. The reducing of cost of debt in politically connected firms is a consequence based on shared resource knowledge of Political connection directors in law, finance and government procurement contracts for favorable government policies and tax rebates. The results of this study significantly contribute to the literature through providing evidence from China. Keywords: Politically Connected Firms; politically connected directors; Cost of Debt JEL Classifications: D72, H63, G32 DOI: https://doi.org/10.32479/ijefi.7561